PENGARUH ISLAMIC CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT - Melinda Rahman; Dini Rosdini; Indri Yuliafitri (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2020)
This study aims to analyze the effect of Islamic corporate governance on earnings management. The research method used in this research is quantitative descriptive method. The population in this study were all Islamic banks in Indonesia and Malaysia, as many as 25 Islamic banks. The data analysis technique used is panel data analysis to answer the formulation of research problems related to the influence of Islamic corporate governance on earnings management. Based on the results of statistical tests, Islamic corporate governance consisting of sharia supervisory boards, board of commissioners and managerial ownership has the following relationship: sharia supervisory board, board of commissioners and managerial ownership does not significantly influence earnings management at Islamic Commercial Banks (BUS) in Malaysia and the State of Indonesia